Influence of the Operation of the Power Units of Thermal Power Plants in the Maneuvering Mode on the Aging Rate of Power Equipment - Chernousenko, Olga Yuryevna; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
A peculiar feature of the power engineering in Ukraine is a shortage of maneuvering powers; therefore the Nuclear Power Plants available in Ukraine have to use pulverized-coal blocks designed for the basic operation to meet peak loads and for the control on the whole. The current state of power generating equipment was analyzed in compliance with the normative documents approved by the Ministry of Power Engineering and Fuel Industry of Ukraine. The influence of the operation of power units of 200–300 MW in the maneuvering mode has been studied and the predicted residual life in the normal operation mode and in the maneuvering mode of daily start-stop has been calculated. The ageing rate indicators have been calculated and it was established that the equipment aging rate in the maneuvering mode increases three to eight times in comparison with that at the normal operation. It was established that the operation in this mode requires the normative substantiation: the key parameters and criteria of operating conditions should be defined, the software for the technical diagnostics should be introduced, and the additional control (examination) of the technical state of power equipment should be arranged and exercised and the obtained results must be processed. The measures should be taken to provide the safe operation and exercise control over the aging of power plants during the reassigned operation life. Due to this fact and taking into consideration the current state of the equipment the operation in the maneuvering mode in undesirable and requires the development of special normative base, because the available key assets are subjected to a considerable wear.